Heavy metal toxicity in poultry: a comprehensive review - Aljohani, Abdullah S. M. (Frontiers in Veterinary Science, 2023)
Arsenic (As), lead (Pb), cadmium (Cd), and mercury (Hg) have been recognized as most toxic heavy metals that are continuously released into the environment, both from natural sources and from anthropogenic production of fertilizers, industrial activities, and waste disposal. Therefore, As, Cd, Hg, and Pb are found in increasing concentrations in bodies of water, fodder, feed, and in the tissues of livestock, including poultry, in the surroundings of industrial areas, leading to metabolic, structural, and functional abnormalities in various organs in all animals. In poultry, bioaccumulation of As, Pb, Cd, and Hg occurs in many organs (mainly in the kidneys, liver, reproductive organs, and lungs) as a result of continuous exposure to heavy metals. Consumption of Cd lowers the efficiency of feed conversion, egg production, and growth in poultry. Chronic exposure to As, Pb, Cd, and Hg at low doses can change the microscopic structure of tissues (mainly in the brain, liver, kidneys, and reproductive organs) as a result of the increased content of these heavy metals in these tissues. Histopathological changes occurring in the kidneys, liver, and reproductive organs are reflected in their negative impact on enzyme activity and serum biochemical parameters. Metal toxicity is determined by route of exposure, length of exposure, and absorbed dosage, whether chronic and acute. This review presents a discussion of bioaccumulation of As, Cd, Pb, and Hg in poultry and the associated histopathological changes and toxic concentrations in different tissues.